Tricuspid regurgitation in the setting of LVAD support - Mitra, Ananya; Siddique, Aleem (Frontiers in Cardiovascular Medicine, 2023)
Tricuspid valve regurgitation (TR) is a common complication of end-stage heart failure. Increased pulmonary venous pressures caused by left ventricular (LV) dysfunction can result in a progressive dilation of the right ventricle and tricuspid valve annulus, resulting in functional TR. Here, we review what is known about TR in the setting of severe LV dysfunction necessitating long-term mechanical support with left ventricular assist devices (LVADs), including the occurrence of significant TR, its pathophysiology, and natural history. We examine the impact of uncorrected TR on LVAD outcomes and the impact of tricuspid valve interventions at the time of LVAD placement, revealing that TR frequently improves after LVAD placement with or without concomitant tricuspid valve intervention such that the benefit of concomitant intervention remains controversial. We summarize the current evidence on which to base medical decisions and provide recommendations for future directions of study to address outstanding questions in the field.